Protective Effect of Garlic Extract (Allium sativum L.) on the Liver Tissue of Arsenic-Induced Channa punctatus: Protective Effect of Garlic Extract (Allium sativum L.) on the Liver Tissue of Arsenic-Induced Channa punctatus - Das, Titikksha (International Journal of Pharmaceutical & Biological Archive, 2019)
Arsenic in its inorganic form is toxic and can cause severe health effects including cancers. In several in vitro experiments, arsenic exposure has shown multiple effects at the molecular level. However, the proper understanding of the role of arsenic in the cause of these diseases is still limited. In this work, we demonstrated the toxicity effect of sodium arsenite in the liver tissues of freshwater fish Channa punctatus and observed the histopathological as well as surface ultrastructural changes on it. A simultaneous study was performed to observe the protective effect of garlic extract (Allium sativum L.) on the liver tissue of arsenic-induced C. punctatus. The liver tissue of the control group showed a normal histoarchitecture. The arsenic-exposed liver tissue revealed hepatic lesions in the form of cloudy swelling of hepatocytes, vacuolar degeneration, karyolysis, dilation of sinusoids, and nuclear hypertrophy. Lesser hepatic alternation was observed in the liver tissue of arsenic-exposed C. punctatus concurrently treated with garlic extract. The protective effect of garlic was shown in the normalization of hepatocytes in the arsenic-induced liver tissue.